The demand for crop genetic resources from a national collection - Day-Rubenstein, Kelly; Smale, Melinda (International Food Policy Research Institute, 2003)
Who uses a genebank? What kind of germplasm is requested and for what purpose? How is it in fact “used”? What problems do users identify? This case study seeks to answer these questions with data collected directly from individuals who requested samples from the U.S. National Plant Germplasm System during 1995-1999 for 10 major crops (barley, bean, cotton, maize, potato, rice, sorghum, soybean, squash, and wheat). Genebank accessions are used in many different ways, and large national genebanks receive many requests from international sources.